CLINICAL CASE OF ABO INCOMPATIBLEKIDNEYTRANSPLANTATTHE О. SHALIMOV’S NATIONAL INSTITUTE OFSURGERYAND TRANSPLANTOLOGYIN UKRAINE - Zograbian, R.; Zakordonets, V.; Malik, A.; Zakrutko, O.; Tarasenko, L. (Ukrainian Journal of Nephrology and Dialysis, 2015)
Kidney transplantation is the gold standard for treating end - stage kidney disease. But the lack of cadaveric organ donation in Ukraine makes this operation available only for patients with living related donor. The absence of ABO - compatible living donor in the family is found in 20 - 30% of cases. This is the case for ABO - incompatible transplantation, but it is associated with an increased risk of acute rejection and requires special pre - transplant management. The article describes the first in Ukraine successful case of ABO - incompatible kidney transplantation in A.A. Shalimov’s National Institute of Surgery and Transplantology.